2005
DOI: 10.1042/bj20042091
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana β1,2-xylosyltransferase: an unusual glycosyltransferase with the potential to act at multiple stages of the plant N-glycosylation pathway

Abstract: XylT (beta1,2-xylosyltransferase) is a unique Golgi-bound glycosyltransferase that is involved in the biosynthesis of glycoprotein-bound N-glycans in plants. To delineate the catalytic domain of XylT, a series of N-terminal deletion mutants was heterologously expressed in insect cells. Whereas the first 54 residues could be deleted without affecting the catalytic activity of the enzyme, removal of an additional five amino acids led to the formation of an inactive protein. Characterization of the N-glycosylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 36 publications
3
55
1
Order By: Relevance
“…In addition, we obtained evidence that prexylosylation is important for efficient fucosylation, because mutants lacking xylose residues reveal decreased amounts of core fucose residues in their N-glycans. This contrasts with the report of Bencúr et al (43), which showed that fucosyltransferase activity is inhibited by presence of a xylose residue in the acceptor N-glycans. This apparent inconsistency may have been caused by two GlcNac-terminated antennae used as substrate for their in vitro study.…”
Section: Discussioncontrasting
confidence: 55%
“…In addition, we obtained evidence that prexylosylation is important for efficient fucosylation, because mutants lacking xylose residues reveal decreased amounts of core fucose residues in their N-glycans. This contrasts with the report of Bencúr et al (43), which showed that fucosyltransferase activity is inhibited by presence of a xylose residue in the acceptor N-glycans. This apparent inconsistency may have been caused by two GlcNac-terminated antennae used as substrate for their in vitro study.…”
Section: Discussioncontrasting
confidence: 55%
“…Our data indicate that GALT1 rather than FUT13 is the rate-limiting enzyme. This is supported by the following lines of evidence: (1) GALT1 is expressed in a tissue-specific manner, and its expression levels correlate with the Le a levels of the respective organs; (2) overexpression of GALT1 increases the occurrence of Le a epitopes in tissues with otherwise low Le a contents (e.g., leaves); (3) the catalytic proficiency of GALT1, at least in vitro, is rather low compared with other plant glycosyltransferases (Bencú r et al, 2005;Strasser et al, 2005); (4) while the activities of most other glycosyltransferases involved in N-glycan processing can be readily measured in plant extracts (e.g., Staudacher et al, 1995;Palma et al, 2001;Lé onard et al, 2002;Strasser et al, 2004b), direct detection of endogenous GALT1 activity has not yet been achieved.…”
Section: Le a : A Tissue-specific Structural Element Of Complex Arabimentioning
confidence: 70%
“…This band was identified as GALT1 itself. Since endogenous and heterologous glycoproteins synthesized by Sf21 cells usually lack N-glycans with terminal galactose residues (e.g., Kubelka et al, 1994;Bencú r et al, 2005), we concluded that GALT1 is capable of autogalactosylation during its production in these cells. In Figure 7B, the autogalactosylation of GALT1 was only detectable upon further incubation with recombinant FUT13 in the presence of the donor substrate GDP-fucose.…”
Section: Characterization Of Galactosyltransferase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Expression in Spodoptera frugiperda Sf21 cells was performed exactly as described previously [21]. Briefly, the recombinant transfer vector (1 mg) was co-transfected with 200 ng of BaculoGold viral DNA (BD Biosciences, Erembodegem, Belgium) into Sf9 cells using Lipofectin (Invitrogen) as recommended by the manufacturer.…”
Section: Expression Of Ves V 2 Variants In Insect Cellsmentioning
confidence: 99%